Effect of Cigarette Smoking on Risk of Hip Fracture in Men: A Meta-Analysis of 14 Prospective Cohort Studies - Wu, Zhen-Jie (PLoS One, 2016)
BACKGROUND: Several observational studies have suggested an association between cigarette smoking and risk of hip fracture. However, no formal systematic review or meta-analysis was performed to summarize this risk in men. MATERIALS AND METHODS: A search was applied to MEDLINE, EMBASE, and web of science (up to November 1 2016). All prospective cohort studies assessing risk of hip fracture with the factor of cigarette smoking in men without language restriction were reviewed, and qualities of all included studies were assessed using the Newcastle-Ottawa Scale. Two authors independently assessed literatures and extracted information eligibility, and any disagreement was resolved by consensus. Newcastle-Ottawa quality assessment scale was used to evaluate studies’ quality in meta-analyses. We calculated the RR with 95% CIs in a random-effects model as well as the fixed-effects model using the metan command in the STATA version 12.0 (StataCorp, USA). RESULTS: Fourteen prospective cohort studies were eligible for the present analysis. A meta-analysis of 12 prospective studies showed that the relative risk (RR) for current male smoking was 1.47 [95% confidence interval (CI) (1.28–1.66), p = 0.54; I(2) = 0%]. Subgroup analyses show study characteristics (including geography region, length of follow-up, size of cohorts and study quality) did not substantially influence these positive associations. Eight studies reported the RRs for former smokers compared with never smokers and the pooled RR was 1.15 [95% CI, (0.97–1.34), (I(2) = 0%, p = 0.975)]. CONCLUSIONS: The present meta-analysis of 14 prospective studies suggests that, compared with never smokers, cigarette smoking increases risk of hip fracture in man, specifically in current smokers. However, further larger prospective cohorts with more power or meta-analysis of individual patient data are needed to confirm this association.